Influence of Social Media on Secondary School Students' Learning of Sexual Education In Nigeria - Turnwait Michael (South Sulawesi Education Development (SSED), 2024)
This study investigates the influence of various factors on the knowledge of sexual education among adolescent students in Nigeria, with a particular focus on the role of social media (SM) engagement. A sample of 1,136 participants was surveyed, and logistic regression analysis was conducted to assess the associations between demographic variables, SM use patterns, and content engagement on SM platforms with the knowledge of sexual education. Findings reveal significant associations between several factors and knowledge of sexual education. Older students (aged 15 and above), senior secondary students, and those attending private schools demonstrate higher odds of possessing sexual education knowledge. Notably, participants who engage with SM platforms for 1-3 hours per week exhibit increased odds of having knowledge, while excessive SM use (more than 6 hours per week) is associated with decreased odds of knowledge acquisition. Furthermore, content engagement on SM shows varying associations, with educational content positively correlated with knowledge acquisition, and entertainment content negatively correlated. These results underscore the importance of considering diverse factors, including demographics and SM use behaviors, in promoting sexual education among adolescent populations. Strategies aimed at enhancing sexual education programs should take into account the differential impact of SM engagement and content preferences on knowledge acquisition. Addressing these factors can contribute to the development of more effective interventions for promoting sexual health literacy among adolescents in Nigeria and similar contexts.